Quantum secure patient login credential system using blockchain for electronic health record sharing framework - M. Natarajan; A. Bharathi; C. Sai Varun; Shitharth Selvarajan (Scientific Reports)
Abstract Nowadays, most of the medical records are maintained in a digital format known as Electronic Health Records Sharing (EHRS) framework. Patients have individual login credentials for accessing these medical records. In the BCT, the information about the owner of the block and its dependency over other blocks is maintained in itself. Moreover, each block is linked with its nearby blocks, leading to a network controlled by patients responsible for storing and sharing the information. In healthcare, BCT can help with mobile health apps, monitoring equipment, sharing and keeping of clinical trial data, electronic medical records, and insurance information storage. This study proposes a secure Patient Login Credential System (PLCS) for EHRS. The proposed scheme has been included for block encryption with the symmetric and asymmetric cryptography algorithms with respect to the hospital server and patients. Additionally, the Quantum Secure Trust Protocol (QSTP) is integrated to enhance trust and security between the patient-side and hospital-side, maintaining data integrity and confidentiality. Similarly, the Tune Swarm Optimization (TSO) algorithm is utilized to optimize performance metrics. The security analysis for the proposed scheme has been evaluated with basic security assumptions for information systems like, availability, access control, maintaining forward secrecy, and maintaining data integrity. The proposed scheme demonstrated enhanced security and performance, with IDEA achieving encryption in 58 ms and decryption in 278 ms for a 512-bit block, offering the best performance in terms of encryption speed.